EDUKASI AKTIVITAS FISIK DAN OLAHRAGA DI MASYARAKAT PADA MASA PANDEMI COVID-19 - Kahtan, Muhammad Ibnu; Wicaksono, Arif; Hadi, Didiek Pangestu; Asyhar, Alfan Nur (Universitas Trisakti, 2026)
Coronavirus Disease 2019 (COVID-19) had affected all daily life including physical activity. People still confuse about physical activity and sport, then pandemic make these worse. Several health protocols that implemented in order to prevent COVID-19 transmission had limited community movement and activities. The aim of this community service was sharing latest information in physical activity during pandemic. Community counseling was conducted online using Zoom platform. The target of community counseling was university students, sport exciter, and general population. As many as ninety persons participated in online community counseling. The participants were active in asking and discussing during two hours online event.